On the Noise Hazard Assessment within the Intermediate Range of the High Audible and the Low Ultrasonic Frequencies - ŚLIWIŃSKI, Antoni (Archives of Acoustics, 2016)
In parallel to the ultrasonic noise assessment procedures and research activity in the field there have appeared several papers in the domain of so called high-frequency audiometry which covers the range of frequencies 8–20 kHz. They are important for recognizing the harmfulness and hazard of the audible high frequency sound components in the same range as the one of the low frequency ultrasonic noise. On the other hand there exists a certain inconsequent situation in the general approach to the problem of ultrasonic noise hazard assessment in work places environment which concerns the convention to include the frequency range of 10–20 kHz to the domain of ultrasonics. The range consists of one third octave bands of central frequencies: 10, 12.5, 16, 20 kHz and conventionally is called low frequency ultrasonic noise though at least the components of the two lowest bands are naturally audible by a majority of population (mainly young people).The paper presents a discussion related to some achievements of the two domains and some conclusions which could be useful for a more consequent description of the subject and could be taken into account in the future regulations for the ultrasonic noise assessment in work places environment.